Drawn in : a peek into the inspiring sketchbooks of 44 fine artists, illustrators, graphic designers, and cartoonists /: a peek into the inspiring sketchbooks of 44 fine artists, illustrators, graphic designers, and cartoonists. (2011) - Unknown
No abstract available